Maize-Nutrient-Manager: Use and data collected in 2019-2020 season, Songwe region, Tanzania - Andersson, Jens A; Kilakila, Mukoma Kitundu; Hijbeek, Renske (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The provision of more tailored fertilizer management advice to smallholder farmers critically hinges upon – largely lacking – field-level management data, as management is key to efficient fertilizer use. The Maize-Nutrient-Manager (MNM) mobile phone application collects of such data at scale, and directly converts this data into actionable advice for the farmer. This data document describes the data collected with the MNM application (n=1038 records) in the Songwe region in Tanzania in the 2019-2020 season. In addition, this report provides information on the data collected through farmer Advice Forms (AF) one which the MNM advice was written. As these forms were simultaneously used by farmers as Field Records (FR) of in-season management practices, these forms constitute another source of data (n=723). This report presents some descriptive statistics on MNM use and management practices in the 2019- 20 season, but due to an incomplete data collection process (partially caused by COVID-19 travel restrictions), cannot present extensive analyses of the data collected. Analyses that can identify major yield determining factors and impacts of MNM use will be conducted in 2021, when 2019-20 yield data has been collected through the deployment of MNM (in November and December 2020) just before the start of the 2020-2021 season.